THE REDUCTION OF BOD, COD AND CHROME IN THE TANNING WASTEWATER - Nugroho, Alfani Risman; Anggriyani, Emiliana (MATTER: International Journal of Science and Technology, 2018)
The tannery industry generally uses chrome raw materials in its tanning process. This use results in liquid waste containing chromium. This study aims to determine and analyze the characteristics of the waste from the exhausted chromed tanning process. The material used are sheep skins, which is tanned using conventional methods and the exhausted chrome tanning process. The collected liquid waste is then tested on the parameters of BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), and total chrome. The results of this test are then analyzed using Independent Sample T-Test, which revealed that the use of the exhausted chromed tanning process is capable of producing waste with lower total value of chromium, BOD, and COD, than that of with conventional method. However, those results are still above the applicable wastewater quality standards, so it still requires further processing in order to meet the requirements in Indonesia.